Kawasaki disease in infants below 6 months: a clinical conundrum?. (16th March 2016) - Singh, Surjit; Agarwal, Sikha; Bhattad, Sagar; Gupta, Anju; Suri, Deepti; Rawat, Amit; Singhal, Manphool; Rohit, Manojkumar
Abstract: Aim: Kawasaki disease (KD) is a medium vessel vasculitis of childhood. In infancy KD is often characterized by incomplete and atypical forms. There is paucity of literature on KD in children below 6 months and there are no data from any developing country. This study defines the profile of children with KD below 6 months at our centre. Methods: During January 1994 to March 2015, 460 children were diagnosed with KD and 17 (3.6%) were below 6 months. Diagnosis was based on American Heart Association (AHA) criteria. All children were treated with intravenous immunoglobulin and aspirin; three also received infliximab. Results: Mucosal changes were present in 11 patients (64%); extremity changes in 11 (64%); rash in nine (53%); conjunctival injection in eight (47%); and cervical lymphadenopathy in three (17%). Irritability was noted in 15 patients (88%); four (23%) had respiratory symptoms; and two (11%) had bacille Calmette–Guérin scar reactivation. Fifteen (88%) had incomplete KD. Twelve patients were diagnosed beyond day 10 of illness. Thrombocytopenia was seen in four. Coronary artery abnormalities were present in six (35%) patients. Two children died from disease‐related complications – one of these had giant coronary artery aneurysms. Conclusion: Our data show that incomplete forms of KD are commonly seen in children below 6 months of age, thereby resulting in delayed diagnoses. Pediatricians need to have a high index of suspicion of KD when dealing with a young infant with unexplained fever beyond 5 days. The AHA criteria appear to be inadequate for diagnosing KD in infants below 6 months.